Prince Eugens Waldemarsudde - a total artwork - Li, Yanan 1973- (Arvinius + Orfeus Publishing, 2019)
In this beautiful book Waldemarsudde is presented in all of its colourful spectra. The photographic material takes us on a journey through the art collections, architecture and interiors to the sculptures in the wonderful gardens. Photographer Yanan Li has captured the place over time and throughout changing seasons, the result is a beautiful portrait of Prince Eugen s Waldemarsudde.
Keywords: Prins Eugens Waldemarsudde; Stockholm; Waldemarsudde (Museum : Djurgården, Stockholm, Sweden); Museums / Sweden / Stockholm / History; Eugen / Prince of Sweden / 1865-1947 / Homes and haunts; Stockholm (Sweden) / Buildings, structures, etc; Eugen / Prince of Sweden / 1865-1947; Buildings; Homes; Museums; Sweden / Stockholm; History; Bildband